The legal deposit of digital spatial data in the United Kingdom - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
This paper critically reviews progress and problems in the uptake of digital cartographic data in UK legal deposit libraries over the last few years. The details and effect of the Voluntary Code, introduced from January 2000, are examined, along with the technical, practical and political reasons for its relatively limited effects. Second, the progress map libraries have made in setting up Ordnance Survey digital data systems are examined, along with the problems that have delayed work and the discussions about obtaining other cartographic data sources. The paper concludes by offering suggestions on possible methods of future progress